Load Magnitude and Locomotion Pattern Alter Locomotor System Function in Healthy Young Adult Women - Krajewski, Kellen T.; Dever, Dennis E.; Johnson, Camille C.; Mi, Qi; Simpson, Richard J.; Graham, Scott M.; Moir, Gavin L.; Ahamed, Nizam U.; Flanagan, Shawn D.; Anderst, William J.; Connaboy, Chris (Frontiers in Bioengineering and Biotechnology, 2020)
Introduction: During cyclical steady state ambulation, such as walking, variability in stride intervals can indicate the state of the system. In order to define locomotor system function, observed variability in motor patterns, stride regulation and gait complexity must be assessed in the presence of a perturbation. Common perturbations, especially for military populations, are load carriage and an imposed locomotion pattern known as forced marching (FM). We examined the interactive effects of load magnitude and locomotion pattern on motor variability, stride regulation and gait complexity during bipedal ambulation in recruit-aged females. Methods: Eleven healthy physically active females (18-30 years) completed one-minute trials of running and FM at three load conditions: no additional weight/bodyweight (BW), an additional 25% of BW (BW+25%), and an additional 45% of BW (BW+45%). A goal equivalent manifold (GEM) approach was used to assess motor variability yielding relative variability (RV; ratio of ‘good’ to ‘bad’ variability) and detrended fluctuation analysis (DFA) to determine gait complexity on stride length (SL) and stride time (ST) parameters. DFA was also used on GEM outcomes to calculate stride regulation. Results: There was a main effect of load (p=.01) on RV; as load increased, RV decreased. There was a main effect of locomotion (p=.01), with FM exhibiting greater RV than running. Strides were regulated more tightly and corrected quicker at BW+45% compared (p<.05) to BW. Stride regulation was greater for FM compared to running. There was a main effect of load for gait complexity (p=.002); as load increased gait complexity decreased, likewise FM had less (p=.02) gait complexity than running. Discussion: This study is the first to employ a GEM approach and a complexity analysis to gait tasks under load carriage. Reduction in ‘good’ variability as load increases potentially exposes anatomical structures to repetitive site-specific loading. Furthermore, load carriage magnitudes of BW+45% potentially destabilize the system making individuals less adaptable to additional perturbations. This is further evidenced by the decrease in gait complexity, which all participants demonstrated values similarly observed in neurologically impaired populations during the BW+45% load condition.